An Evaluation of Residence Satisfaction on Window Design of Mass Housing in Hot-Humid Climates: The Case of Famagusta, North Cyprus - HajiAbadi, Soolmaz Abdali (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
Windows are one of the building components, which are not only essential in terms of connecting inside and outside of the building but also for providing daylighting and natural ventilation to interior spaces. In hot-humid climates, windows’ role become more prominent - especially in residences where users spend a considerable amount of time - for supplying proper daylight admittance through the control of sun and ventilation for the elimination of humidity. Considering the increasing amount of mass housing in cities where demand for shelter is continuously up rising, there is more similar type residential buildings appearing, designed with little or no consideration of local climatic issues. This has resulted in the increase of dissatisfied users where there are major complaints relating to improperly lit interior spaces, lack of suitable shading devices to control unwanted sun during lengthy summer seasons, and necessary openings to provide natural ventilation. The aim of this thesis is to understand the problems associated with window design and the level of satisfaction of users in relation to daylighting and ventilation issues in selected residential buildings in Famagusta, North Cyprus through observations and questionnaires with the users. For this purpose, selected criteria such as type of shading device, orientation, size, placement and ratio of windows area to floor area, glazing and opening types have been investigated to understand whether windows have been appropriately used in these apartment type buildings in hot-humid climate. iv The observations and questionnaires prove that in the design of windows, use of appropriate shading devices, windows size, types of windows, placement as well as building orientation can be effective on the performance of windows and affect user satisfaction. Keywords: Window design, Daylighting, Ventilation, Residential Building, Hot-humid climate, Residence satisfaction

ÖZ : Pencere, iç mekanı aydınlatmak ve doğal havalandırmayı sağlamak yanında binanın içi ve dışı arasında görsel bir iletişim kurmayı sağlayan önemli bir yapı elemanıdır. Özellikle sıcak-nemli iklimlerde nemin ortadan kaldırılması amacı ile güneş ve havalandırma kontrolünü sağlamakta önemli görevler üstlendiğini söyleyebiliriz. Özellikle toplu konut örneklerinde doğru pencere tasarımı ve uygulamasının, binalarda enerji tasarrufu sağlamak ve kullanıcıyı memnun etmek açısından önemli olduğunu yapılan araştırmalardan da anlamaktayız. Özellikle kentlerde karşılaşılan ve birbirleri ile cok benzeşen toplu konut örneklerinin pencere tasarımlarına bakıldığında yerel iklim verilerinin az veya hiç dikkate alınmadığı gözlenmektedir. Yanlış doğal havalandırma, uygunsuz genişlikte açıklıklar ve istenmeyen güneşi kontrol etmeyi amaçlayan uygun gölgeleme araçlarının eksikliği, kullanıcı memnuniyetsizliğini oluşturan nedenlerden sayılabilir. Tezin amacı, sıcak-nemli iklime sahip Gazimağusa kentinde toplu konut örneklemleri aracılığı ile günışığı ve havalandırma kriterlerinin pencere tasarımında ne kadar etkili olduğunu anlamaktır. Bu amaçla, pencere boyutları ve tipleri yanında yerleşimi, pencere/taban oranı, gölgeleme araçları gibi alt kriterler belirlenerek, kullanılan pencerelerin sıcak-nemli iklim gereklerine göre tasarlanıp tasarlanmadığı gözlemler ve kullanıcı memnuniyeti üzerinden tartışılmaktadır. Bu kapsamda yapılan gözlem ve anketlerin sonucunda pencere tasarımının ve ona uygun gölgeleme elemanlarının kullanılmasının, pencere boyutları ve tipi yanında hangi yönde konumlandığının kullanıcı memnuyiteni etkilediği ortaya çıkmıştır. Anahtar Kelimeler: Pencere tasarımı, Günışığı, Havalandırma, Konut, Sıcak-nemli iklim, Kullanıcı memnuniyeti
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2014. Supervisor: Assist. Prof. Dr. Pınar Uluçay.
Keywords: Architecture; Wındows - Buildings - Cyprus, North; Window design; Daylighting; Ventilation; Residential Building; Hot - humid climate; Residence satisfaction